199k views
2 votes
F(x) = -2x^2-4x+11
in the standard form
f(x) = a(x – h)^2+k

2 Answers

4 votes

Answer:

f(x) = - 2(x + 1)² + 13

Explanation:

f(x) = - 2x² - 4x + 11

f(x) = a(x - h)² + k

a = - 2, b = - 4, c = 11

h = -
(b)/(2a)

h = -
(-4)/(2(-2)) = - 1

k = - 2( - 1)² - 4( - 1) + 11 = 13

f(x) = - 2(x + 1)² + 13

User Karandeep Singh
by
5.1k points
6 votes

Explanation:

f(x) = -2x^2-4x+11

y = -2(x+1)²+13

Use the vertex form, y=a(x−h)²+k, to determine the values of a, h, and k.

a= -2

h= 1

k= 13

Final answer is, f(x) = -2(x - 1)² + 13

User Bedo
by
5.1k points